Entre subjetividade e alteridade : análise do discurso político na prosa de Gabriela Mistral - Rojas, Gabriel Arturo Farías (2018)
The objective of this Masters Dissertation is to do a qualitative analysis of Gabriela Mistral’s Political Discourse, which has been taken from three different sources. This Edition involves two decades for Mistral’s Discourse (1920 and 1930). To do this, an inter- and transdisciplinary approach (Discourse and Enunciation, Literary Theory and Criticism, Political Philosophy, Social Sciences and Latin-American Studies) will be followed in order to reflect on Gabriela Mistral as a writer who has been metonymically realized in World Literature. The latter takes place by means of a Colonial Myth imposed on society, which, based on Republicanism, forgets about her contribution to both the Iberoamerican Continent and the Western World in general terms. Thus, new perspectives are necessary and they can be reached by acknowledging the author’s subjectivity, which will help to notice a plethora of contradictions belonging to a decentered subject within the cronotopical story of her own biography. Keywords: Gabriela Mistral – Political Discourse – Prose – Subjectivity and Otherness – Colonial Myth